2000
DOI: 10.2460/javma.2000.217.43
|View full text |Cite
|
Sign up to set email alerts
|

Use of physiatry as the sole treatment for three paretic or paralyzed dogs with chronic compressive conditions of the caudal portion of the cervical spinal cord

Abstract: Physiatry alone was used to treat 3 large (30- to 40-kg [66 to 88 lb]) mature (6- to 9-year-old) dogs that were tetraparetic or tetraplegic. All 3 dogs had myelographic evidence of multiple chronic compressive extradural lesions of the caudal portion of the cervical spinal cord. All dogs improved substantially after a course of intensive physical treatment. For 2 dogs, an abbreviated treatment regimen was continued by the owners after the dogs were discharged. Both of these dogs regained and retained normal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Other complications from prolonged recumbency include periarticular fibrosis, cartilage atrophy, and osteopenia. Physiotherapy and active massage therapy has been described as a useful adjunct in paralyzed patients . Passive range of motion exercises should be performed in recumbent patients to prevent these complications.…”
Section: Recumbencymentioning
confidence: 99%
See 1 more Smart Citation
“…Other complications from prolonged recumbency include periarticular fibrosis, cartilage atrophy, and osteopenia. Physiotherapy and active massage therapy has been described as a useful adjunct in paralyzed patients . Passive range of motion exercises should be performed in recumbent patients to prevent these complications.…”
Section: Recumbencymentioning
confidence: 99%
“…Physiotherapy and active massage therapy has been described as a useful adjunct in paralyzed patients. 123 Passive range of motion exercises should be performed in recumbent patients to prevent these complications. Passive range of motion exercises are important for maintaining joint range of motion, maintaining cartilage health, minimizing muscle contracture, and maintaining muscle elasticity.…”
Section: Recumbencymentioning
confidence: 99%
“…Case studies have reported on the use of physical interventions to increase mobility after canine SCI; stretching in the form of traction 12 , passive ROM, isometric stretch and locomotor training 13 have been used. Any improvements reported in these studies were not attributed solely to the physical interventions employed.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbed energy causes an active tissue reaction that leads to a sequence of local and general effects (Lambrechtsten et al, 1992). Physical therapy can replace or reduce the use of analgesics and steroids (Speciale and Fingeroth, 2000). Chronic non-diagnosed and untreated spondyloarthritis give paresis and paralysis of dubious prognosis.…”
Section: Clinical Criteriamentioning
confidence: 99%